Research Interests Among Students of the Distance-Learning Degree in Basic Education - Guerra Gómez, Sandra Lucia (Rastros Rostros, 2014)
This article shares part of the results of a research study that aimed to systematize certain aspects of the final projects undertaken by students in the Degree of Basic Education with an emphasis on Mathematics, Humanities and the Spanish Language at the Universidad Pedagógica y Tecnológica de Colombia (uptc) from 2008 to 2011. The study used a documentary-style methodology for informational purposes. Information was collected through a generated file, which was created based on students’ research work, thereby making it possible to determine the research interests, areas, and most commonly chosen subjects and topics for research, and correlate these with students’ locations in different regional centers of distance education. The strategy involved creating a database with the information collected. From this, qualitative and quantitative data was generated, then systematized and interpreted for presentation to the academic community. It could be concluded that students choose to conduct research in the Spanish language due to an interest in solving reading and writing learning problems among the populations that the research is based on. Theseprojects were registered in the research area titled Classroom and School. The projects were also chosen because this research area aims to develop learning processes based on problems found in educational contexts where university extension activities are undertaken in the Basic Education Degree.
Keywords: subjects; research interests; area of research; reflection; systematization